Impoliteness Strategies used in the Movie "Easy A" - Jojor Romanna Simanjuntak; Ambalegin Ambalegin (Musamus Journal of Language and Literature, 2022)
This study aimed to analyze the methods employed in Easy A movie. This research is proposed by Culpeper (2011) theory. The researchers used the descriptive qualitative method to analyze the impoliteness strategies in this study. The subject of the research is â€œEasy Aâ€ movie. In this study, data was gathered by using an observational methodology and non-participatory technique. Next, the data was analyzed with the pragmatic identification method. During this study, the researchers identified 16 utterances. As a result of their studies, the researchers discovered five types of impoliteness, including (4) bald on record impoliteness, (5) positive impoliteness, (4) negative impoliteness, (2) mock politeness or sarcasm, and (1) withhold politeness. The most common strategy used by the Easy A movie was positive impoliteness and negative impoliteness.